Social Accounting and Tax Accountability: An Interpretive Study of the Majapahit Empire - Anto, Andri; Nuraini, Fitri (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
The purpose of this paper is to provide evidence that accounting practices and tax accountability have been implemented in the ancient kingdom. This paper uses a qualitative approach and an interpretive study as a method. Data were collected through interviews with informants who are experienced in the history of the ancient kingdom, observations on the Majapahit kingdom site, and librarian research. The results prove that tax accountability during the Majapahit kingdom has been implemented and is under the king's policies. Besides that, social accounting practices during the Majapahit Empire had grown and developed as a result of economic and trade activities that experienced rapid growth. Besides that, the absolute king's power in regulating his people in all fields.